2022
DOI: 10.3390/biom12070983
|View full text |Cite
|
Sign up to set email alerts
|

P2 Receptors: Novel Disease Markers and Metabolic Checkpoints in Immune Cells

Abstract: Extracellular ATP (eATP) and P2 receptors are novel emerging regulators of T-lymphocyte responses. Cellular ATP is released via multiple pathways and accumulates at sites of tissue damage and inflammation. P2 receptor expression and function are affected by numerous single nucleotide polymorphisms (SNPs) associated with diverse disease conditions. Stimulation by released nucleotides (purinergic signalling) modulates several T-lymphocyte functions, among which energy metabolism. Energy metabolism, whether oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 197 publications
0
5
0
Order By: Relevance
“…Thus, P2Y11R activation may also protect blood vessels from vascular injury induced from low pO 2 levels. In particular, the P2Y11 receptor, activated by ATP, has anti-inflammatory actions which could be implicated in endothelial cell protection in cardiovascular diseases [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, P2Y11R activation may also protect blood vessels from vascular injury induced from low pO 2 levels. In particular, the P2Y11 receptor, activated by ATP, has anti-inflammatory actions which could be implicated in endothelial cell protection in cardiovascular diseases [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…P2X7R expression is not restricted to brain tissue, and P2X7Rs can be found throughout the body, including the peripheral immune system (e.g., macrophages, T cells) [ 119 , 138 , 139 ]. Suggesting its potential as a diagnostic marker, a recent study by Giuliani et al showed that P2X7Rs can be shed into circulation, which seems to be increased under inflammatory conditions.…”
Section: The Role Of P2x7rs During Seizures and Epilepsymentioning
confidence: 99%
“…While, activation of ComC leads to the release of C3 and C5 cleavage fragments—C3a and C5a anaphylatoxins that activate specific G-protein coupled receptors C3aR and C5aR, respectively, eATP released into extracellular space becomes a potent signaling mediator that activates ion-gated purinergic receptors from P2X family—P2X7 and P2X4 [ 19 ]. Receptors for C3a, C5a, and eATP are coupled to a superoxide-generating enzyme Nox2 complex that produces reactive oxygen species (ROS) [ 11 ], a potent activator of an intracellular PRR that is Nlrp3 inflammasome [ 12 ].…”
Section: A Novel Role For Reactive Oxygen Species (Ros) As Signaling ...mentioning
confidence: 99%
“…All these signaling pathways potentiates ROS-mediated activation of Nlrp3 inflammasome. In addition, Nlrp3 inflammasome may be additionally activated by cytosolic changes in concentration of K + and Ca 2+ as seen after stimulation of P2X7 and P2X4 receptors by eATP [ 19 , 20 ].…”
Section: A Novel Role For Reactive Oxygen Species (Ros) As Signaling ...mentioning
confidence: 99%